ANALISIS POTENSI GERAKAN TANAH DI DESA SIRNARESMI KABUPATEN SUKABUMI - Nauli, Josua Kelpin; Subagio, Yukiko Vega; Mokoginta, Nabilla Kirana (Politeknik Negeri Jakarta, 2019)
AbstractGeological phenomena of this kind is not the first time in the historical records, but still not maximizing the process of disaster management and the map of the land area of landslide caused by hilly geographical conditions, land Lanau, forest conditions planted Grain or crops, even by the human cause of illegal logging, as well. Therefore, this research aims to analyze the stability of slope based on data from the BPBD Sukabumi in the form of slope, morphology, class slopes, weight of the contents of land, soil cohesion and deep friction corners. The analysis was conducted with the help of GeoStudio 2012 software application. The results showed based on an analysis of 19 potentially landslides with a range SF 0530 – 0997 indicating the parameters used by the shear angle of 25 º and the soil weight of 13.4 kN/m³Keywords : Slope stability, Landslide, GeoStudio, Sukabumi.AbstrakFenomena geologi semacam ini bukan kali pertama dalam catatan sejarah, akan tetapi masih belum maksimalnya proses penanggulangan bencana dan rambu peta kawasan tanah longsor yang disebabkan kondisi geografis berbukit, tanah lanau, kondisi hutan yang ditanami padi-padian atau tanaman palawija, bahkan oleh sebab manusia sendiri dengan pembalakan liar. Oleh karena itu penelitian ini bertujuan untuk menganalisis stabilitas lereng berdasarkan data dari BPBD kabupaten Sukabumi berupa kemiringan lereng, morfologi, kelas lereng, berat isi tanah, kohesi tanah dan sudut gesek dalam. Analisis dilakukan dengan bantuan aplikasi software GeoStudio 2012. Hasil penelitian berdasarkan analisis 19 wilayah berpotensi longsor dengan range SF 0.530 – 0.997 menunjukkan parameter yang digunakan sudut geser 25º dan berat isi tanah 13.4 kN/m³.Kata kunci : Kemiringan lereng, Tanah longsor, GeoStudio, Sukabumi.